2007
DOI: 10.1590/s1413-78522007000100002
|View full text |Cite
|
Sign up to set email alerts
|

Fatores genéticos e ambientais envolvidos na degeneração do disco intervertebral

Abstract: A etiologia da degeneração do disco intervertebral (DDI) ainda não está totalmente esclarecida. O gene do receptor da vitamina D (VDR) tem sido apontado como um dos possíveis envolvidos no surgimento das discopatias. Por outro lado, este estudo relaciona pela primeira vez, a participação dos genes das glutatião transferases M1 e T1 (GSTT1 e GSTM1), responsáveis pela inativação dos componentes do cigarro, na DDI. Foi extraído DNA de leucócitos de 66 pacientes e 88 controles, pareados por gênero e idade. O polim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
0
7
0
3
Order By: Relevance
“…Women have the mission of reconciling domestic tasks and professional activities, increasing biomechanical requirements, which makes them more susceptible to ergonomic aggressions, especially repetitiveness, vicious positions and prolonged work 2,9 , probably contributing to a higher female prevalence among patients with low back pain in our study. Several studies report age as risk factor for low back pain 2,5 . With aging, the intervertebral disk looses its hygroscopic feature, suffering progressive dehydration and consequent degeneration, and the spine starts to present progressive instability and pain in the affected region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Women have the mission of reconciling domestic tasks and professional activities, increasing biomechanical requirements, which makes them more susceptible to ergonomic aggressions, especially repetitiveness, vicious positions and prolonged work 2,9 , probably contributing to a higher female prevalence among patients with low back pain in our study. Several studies report age as risk factor for low back pain 2,5 . With aging, the intervertebral disk looses its hygroscopic feature, suffering progressive dehydration and consequent degeneration, and the spine starts to present progressive instability and pain in the affected region.…”
Section: Discussionmentioning
confidence: 99%
“…With aging, the intervertebral disk looses its hygroscopic feature, suffering progressive dehydration and consequent degeneration, and the spine starts to present progressive instability and pain in the affected region. These problems occur in any spinal region, however they are more common between the fourth and fifth lumbar vertebrae and between the fifth lumbar and first sacral vertebrae 5,10 . The relation between years working in the same sector and the prevalence of low back pain is justified as a function of daily body requirements to perform professional activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os genes do receptor da vitamina D e da glutatião transferases M1 e T1, bem como o hábito de fumar, são fatores genéticos e ambientais envolvidos na degeneração do disco intervertebral (40) . Oliveira et al concluíram que as fibras nervosas do tipo III são mais frequentes na região anterior; as fibras dos tipos II e IV são mais frequentes na região posterior; e as fibras do tipo I não apresentaram diferenças entre a região anterior e a posterior; além disso, o disco degenerado tem mais fibras nervosas que o disco normal (41) . Demange et al estudaram o ligamento da cabeça do fêmur e concluíram que o mesmo influi limitando a adução do quadril (42) .…”
Section: Ortopediaunclassified
“…However, the etiology of degenerative disc disease (DDD) is complex. Although environmental, ergonomic, and anthropometric factors have traditionally been determined as causes, several studies have suggested that genetic factors or familial predisposition contribute to the degeneration and consequent herniation of intervertebral discs (Battié et al, 2004;Brioni Nunes et al, 2007;Zhang et al, 2008;Eser et al, 2010;Paz Aparicio et al, 2011).…”
Section: Introductionmentioning
confidence: 99%